PENCIPTAAN BUKU ILUSTRASI KAIN SASIRANGAN SEBAGAI UPAYA PROMOSI SENI BUDAYA BANJARMASIN KEPADA REMAJA - Wijaya, Tonny Aries; Fianto, Achmad Yanu Alif; Hidayat, Wahyu (Jurnal Art Nouveau, 2015)
Abstract: The goal of the design creation illustrated book Sasirangan fabrics are promotional efforts, provide more information about the fabrics Sasirangan for young people, especially teenagers get information about Cain Sasirangan and more loving culture of the region. The study was conducted using qualitative methods is by doing interviews, observation, documentation, and literature to obtain data that is used as a conception of making this illustrated book. The concept gained through data analysis is the specialty of Thousand Rivers. Descriptions of the concept of "Privileged Thousand Rivers" represents the meaning of Cain Sasirangan and Banjarmasin. Sasirangan cloth is cultural heritage, has a unique characteristic of the manufacturing process and has a magical value in ancient times, while Banjarmasin is the capital of the province of South Kalimantan in the city where there are Kampung Sasirangan, and the city has many streams. Privileged by (KBBI) are special properties. Special is the typical, outstanding, other than the other. From concept which has been described above, teens can hope to know more about intangible cultural heritage, distinctive culture Banjar Cain Sasirangan. Results of the creation of this book is to preserve local cultural heritage in Banjar, provide insight to recognize among adolescents in fabrics Sasirangan.Â Keywords: Manufacture, Creation, Book, Illustration, Cloth Sasirangan, Arts Culture Banjarmasin, Teens.